Oxford partial knee replacement by microplasty instrumentation: Indian evidence - Sancheti, Mukesh (International Journal of Research in Orthopaedics, 2020)
Background: There is increasing evidence in support of unicondylar knee replacement (UKR) as a superior surgical modality in a select group of patients of osteoarthritis knee. Oxford knee is one type of UKR with fully congruent, mobile bearing designed to minimize wear. This prospective study describes 5-year results of partial medial compartment knee replacement in 92 Indian cases by microplasty instrumentation. Methods: All 92 cases were operated by a single surgeon. Mean follow up was 5 years. In all cases oxford mobile bearing medial unicondylar knee prosthesis was implanted using minimally invasive surgical technique and the cases followed up. Results: Mean oxford score at the end of 5 year was 43. Patient satisfaction index at the end of 5 year was 98%. Mean maximum flexion was 125 degrees. Incidence of revision was 1.9. No deep or superficial infections were encountered. Average hospital stay was 3 days. Conclusions: There are variations in Indian patients as per size of implants, stay and similarities regarding less blood loss, improved oxford knee score, good range of motion, less morbidity, higher postoperative patient satisfaction and early getting back to work. Oxford partial knee replacement by microplasty instrumentation done in carefully selected patients with proper surgical technique gives excellent functional outcome and superior patient satisfaction.